Manajemen Pembelajaran Guru Pendidikan Jasmani Sekolah SMP di Kota Bengkulu - Lismana, Oetari; Haryono, Mimpira; Martiani, Martiani (Prodi Administrasi Pendidikan, Universitas Pendidikan Mandalika, 2024)
Abstract. The city of Bengkulu is located in the southwest part of Sumatra Island and is on the west coast of the southern part of Sumatra Island which is directly opposite the Indian Ocean coastline on the west side of the province. Bengkulu City consists of 9 districts, 1 municipality, 128 sub-districts, 172 sub-districts and 1341 villages. Through the Department of Education, and in line with government programs in the 2014/2015 academic year, most junior high schools in the Bengkulu city area have implemented a new curriculum, namely the 2013 curriculum. The aim of this research is to find out a direct description of learning management carried out by education teachers. physical, sports and health Elementary schools in Bima City. Data collection used observation, interview and documentation techniques. The data sources were taken from supervisors, school principals, teachers and students. Data validity was obtained by triangulation. Data were analyzed by (1) data reduction, (2) data presentation, and (3) drawing conclusions. The focus of this research is learning management carried out by junior high school physical education, sports and health teachers in the city of Bengkulu which includes three stages, namely (1) learning planning, (2) implementing learning, and (3) carrying out evaluation.Keywords: Physical Education, Sports and Health Management.Abstrak. Kota Bengkulu terletak di bagian Barat Daya Pulau Sumatera dan berada di pantai barat bagian Selatan Pulau Sumatera yang berhadapan langsung dengan garis pantai Samudera Hindia di sisi barat provinsi tersebu. Kota Bengkulu terdiri dari 9 kabupaten, 1 kotamadya, 128 kecamatan, 172 kelurahan, dan 1341 desa. Melalui Dinas Pendidikan, dan seiring dengan program pemerintah pada Tahun Pelajaran 2014/2015 sebagian besar SMP yang ada di wilayah kota Bengkulu telah memberlakukan kurikulum baru yaitu kurikulum 2013. Tujuan dalam penelitian ini adalah untuk mengetahui deskripsi secara langsung tentang manajemen pembelajaran yang dilaksanakan oleh guru pendidikan jasmani, olahraga dan kesehatan Sekolah dasar di Kota Bima. Pengumpulan data menggunakan teknik observasi, wawancara, dan dokumentasi.. Adapun sumber data diambil dari pengawas, kepala sekolah, guru, dan siswa. Validitas data diperoleh dengan cara triangulasi. Data dianalisis dengan cara (1) reduksi data, (2) penyajian data, dan (3) penarikan simpulan. Fokus penelitian ini adalah manajemen pembelajaran yang dilakukan oleh guru pendidikan jasmani olahraga dan kesehatan sekolah menengah pertama di kota Bengkulu yang meliputi tiga tahapan yaitu (1) perencanaan pembelajaran, (2) pelaksanaan pembelajaran, dan (3) pelaksanakan evaluasi.Kata Kunci: Manajemen Pendidikan Jasmani, Olahraga dan Kesehatan .